Study area fishing in selat air hitam Kepulauan meranti district riau province - Eka Fitriani; Alit Hindri Yani; Ersti Yulika Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in Selat Air HitamKepulauanMerantiDistrict ProvinceRiau, used survey method, and the purpose was to determine the existing fishing areas in Selat Air Hitam. From the research,there isonepointthe fishing areawith the best catches throughout the year, that isat the pointof 560 03.0' N – 1020 54’’ 18.5’ E, this point is located close to the village of Repan ,fishing gearusedgombangandlongline, but it catches in the waters of the Selat Air Hitam has various kinds of seafood ranging from fish to shrimp (Penaus) . That affect the extent of the catch in the waters it is a state of the marine environment , because if the water is polluted, the number of fish in the waters will be very few fish in the catch and fishing are also not as they had hoped , the Selat Air Hitam is included in the potential region make an arrest, it can be of varying catches of fishermen.Keywords : fishing area , fishing gear , Selat Air Hitam